Status of woodland caribou in western north America - Edmonds, E. Janet (Rangifer, 1991)
A review of current population size and trends of woodland caribou (Rangifer tarandus caribou) in seven jurisdictions in western North America shows a wide range of situations. A total maximum population estimate of woodland caribou west of the Ontario/Manitoba border is 61 090. Of 44 herds or populations described in this review: 14 are stable; two are stable to slightly decreasing; four are decreasing; four are increasing; and 22 are of unknown status. Caribou are classified as a threatened species in Alberta and as an endangered species in Washington/Idaho. The decline of caribou in North America following settlement (Bergerud, 1974) has continued along the southern edge of woodland caribou distribution. Direct loss of habitat to logging, mines and dams continued throughout the I960s, 1970s and 1980s. The secondary effects of these habitat changes, (i.e. increased roads leading to increased hunting and poaching, and increased early succession habitat leading to increased alternate prey/predator densities) has led in some cases to the total loss or decreased size of local herds. Three ecotypes of woodland caribou are described and their relative distribution delineated. These ecotypes live under different environmental conditions and require different inventory and management approaches. Woodland caribou herds in northern B.C., Yukon and N.W.T. generally are of good numbers and viable (stable or increasing), and management primarily is directed at regulating human harvest and natural predation to prevent, herd declines. Land use activities such as logging or energy development are not extensive. Managers in southern caribou ranges stress the need for a better understanding of caribou population stability within mixed prey/predator regimes; how habitat changes (eg. through logging) affect these regimes; and how to develop effective land use guidelines for resource extraction that can sustian caribou populations and maintain resource industries. Caribou managers have suggested that herds may be priorized for research and management efforts. Unstable, remnant populations may be left to their own fate. The limited research dollars available and difficult management decisions should be applied to caribou herds that are apparently sustainable and provide the greatest potential for long-term viability.